Conceptos de termodinámica entendidos desde la experimentación (calor, temperatura, energía) - Osorio Meneses, Jhon Raul; Patiño Leiva, Sandra Johanna (Revista Científica, 2011)
In a group of tenth grade students of the Institucion Educativa Distrital OEA the most fundamental concepts of thermodynamics and difficult to internalize, in the first part examined the preconceptions that were formed by the context, culture, society, family, school, and more. As expected the concepts of heat, temperature, and energy the commonly used relate to everyday things and the same, so in the field of education becomes a problem because meanings of common speech mixed with physical experiments were performed subsequently gave transitions and lead to conceptual clarification.